Importance of Benzo(a)pyrene in biological systems and its biodegradation - Romero-Balboa-Osorio, Adriana; Alatorre-Cruz, Julia María; Carreño-López, Ricardo; García-García, Silvia María del Carmen; Marín-Cevada, Vianey (REVISTA TERRA LATINOAMERICANA, 2023)
Benzo(a)pyrene (BaP) is a highly distributed molecule in ecosystems and a component of products that are used and consumed regularly. Recent studies have shown this xenobiotic metabolized by organisms forming carcinogenic metabolites, as well as having genotoxic and teratogenic ef fects associated with infertility and endocrine disorders. Similarly, due to its dispersion and bioaccumulation, this molecule can severely damage various ecosystems. Therefore, the objective of this study is to conduct a systematic review to demonstrate the importance of BaP in biological systems and its biodegradation as an alternative to bioremediation.